Evaluating the clinical appropriateness of nurses' prescribing practice: method development and findings from an expert panel analysis. Issue 6 (30th November 2007) - Latter, Sue; Maben, Jill; Myall, Michelle; Young, Amanda
Abstract : Background: The number of nurses independently prescribing medicines in England is rising steadily. There had been no attempt systematically to evaluate the clinical appropriateness of nurses' prescribing decisions. Aims: (i) To establish a method of assessing the clinical appropriateness of nurses' prescribing decisions; (ii) to evaluate the prescribing decisions of a sample of nurses, using this method. Method: A modified version of the Medication Appropriateness Index (MAI) was developed, piloted and subsequently used by seven medical prescribing experts to rate transcripts of 12 nurse prescriber consultations selected from a larger database of 118 audio-recorded consultations collected as part of a national evaluation. Experts were also able to give written qualitative comments on each of the MAI dimensions applied to each of the consultations. Analysis: Experts' ratings were analysed using descriptive statistics. Qualitative comments were subjected to a process of content analysis to identify themes within and across both MAI items and consultations. Results: Experts' application of the modified MAI to transcripts of nurse prescriber consultations demonstrated validity and feasibility as a method of assessing the clinical appropriateness of nurses' prescribing decisions. In the majority of assessments made by the expert panel, nurses' prescribing decisions were rated as clinically appropriate on all nine items in the MAI. Conclusion: A valid and feasible method of assessing the clinical appropriateness of nurses' prescribing practice has been developed using a modified MAI and transcripts of audio-recorded consultations sent to a panel of prescribing experts. Prescribing nurses in this study were generally considered to be making clinically appropriate prescribing decisions. This approach to measuring prescribing appropriateness could be used as part of quality assurance in routine practice, as a method of identifying continuing professional development needs, or in future research as the expansion of non-medical prescribing continues.